Residents as Helpers: Peer Counselling in a Long Term Care Facility - France, M. Honoré (Canadian Journal of Counselling and Psychotherapy, 2011)
The program described in this paper demonstrates how peer counselling works in a long term care facility. The program was implemented at Oak Bay Lodge, a 300-bed long term care facility in Victoria, British Columbia, using training materials specifically developed for older people. This paper shows how the peer counselling program functions, and provides anecdotal comments from both participants and a staff member, along with an outline of the training components.